Impeachment : a handbook - Black, Charles L., Jr. (Charles Lund), 1915-2001; Bobbitt, Philip (Yale University Press, 2018)
"Originally published at the height of the Watergate crisis and reissued in 1998, two months before the second impeachment of a U.S. president, Charles Black's Impeachment became the premier guide to the subject of presidential impeachment. Now thoroughly updated, it is essential reading for every concerned citizen." --